(untitled) (Global Journal of Science Frontier Research, 2023)
Chromosomal polymorphism in Drosophila pseudoobscura has been extensively studied in USA populations and moderately in Mexico with around 60 localities. The differences that exist between both entities are notorious in terms of the chromosomal constitution of the populations of each region, thus, the northern populations (USA) present as representative inversions the ST, AR and CH sequences while in the southern ones (Mexico) TL, CU, and SC chromosome arrangements prevail. Assuming that a probable mechanism that has allowed this substitution is the flow generated by the presence of clines or gradients, in this case with a North-South orientation, we set out to find out the existence of these clines, with this objective, 29 populations of this species distributed in four North-South transects were studied. Specimens of D. pseudoobscura captured by attraction with fermenting fruits were transported to the laboratory where an isoline was formed with each female and a larva was extracted from each one, from which the salivary glands were obtained, which once stained revealed the polytenic chromosomes, in which the inversion(s) carried in the third chromosome pair were individually identified, in this way a total of 3439 chromosomes were analyzed.